Optimizing P3HT/PCBM-Based Organic Photodetector Performance: Insights from SCAPS 1D Simulation Studies - Alali, Ahmet Sait; Oduncuoglu, Murat; Touati, Farid (MDPI, 2024)
Organic electronics have great potential due to their flexible structure, high performance, and their ability to build effective and low-cost photodetectors. We investigated the parameters of the P3HT and PCBM layers for device performance and optimization. SCAPS-1D simulations were employed to optimize the thicknesses of the P3HT and PCBM layers, investigate the effects of shallow doping in the P3HT layer, and assess the influence of the back contact electrode's work function on device performance. Furthermore, this study explored the impact of interface defect layer density on the characteristics of the device. Through systematic analyses, the optimal parameters for enhancing device responsivity were identified. The findings indicate that a P3HT layer thickness of 1200 nm, a PCBM layer thickness of 20 nm, and a back contact electrode with a work function of 4.9 eV achieve the highest responsivity. Notably, at a bias of -0.5 V, the responsivity exceeds 0.4 A/W within the wavelength range of 450 nm to 630 nm. These optimized parameters underscore the significant potential of the developed device as an organic photodetector, particularly for visible light detection.
Keywords: SCAPS 1D; P3HT; PCBM; photodetector; optimization; responsivity; DYNAMICS; Chemistry; Science & Technology - Other Topics; Materials Science; Physics